عناصر القصدية والإعلامية في فهم الأحاديث النبوية في كتاب الأربعين النووية : دراسة وصفية وتحليلية دلالية - Mardiana Binti Mat Ishak (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
The present study seeks to analyse the prophetic discourse in the light of textual linguistics in order to investigate the elements of intentionality and informativity. The researcher chose for the analysis 42 hadiths from the Book of Forty Hadiths by Imam An-Nawawi, which contains four Qudsi hadiths and 38 other hadiths. The analysis of intentionality was applied to 20 hadiths and that of informativity to 22 hadiths. The purpose of the study is to demonstrate the intentionality and informativity elements in the Prophets hadiths from linguistic and communicative aspects, their importance in understanding the meaning the Prophet intended to convey and the interaction of recipients with this prophetic discourse. The study reveals a number of findings; the intention in the hadiths emerged in the words of the Prophet s.a.w including metaphors and rhetorical style, the direct or indirect understanding of the Prophet's words, the elements of intentionality and informativity in showing recipients' understanding of hadiths from a linguistic perspective and the theory of intentionality and informativity. Moreover, scholars of rhetoric (Balaghiyun) investigated the concept of intentionality when talking about the meaning of statements, the meaning of meaning, truth and metaphor and figurative meaning. Informativity is a common term in modern times, but among previous scholars it is reflected in several terms such as statement and understanding, while informativity was considered to be of three levels. The findings also reveals that informativity in the words of the Prophet s.a.w is often found in the second level where there are several possibilities in the mind of the recipient. It is therefore important to know the context in which each hadith was said by the Prophet in order to understand it correctly. The study of the religious discourse, especially the Prophets hadiths, through textual linguistics, has an impact on the understanding of hadiths and their intentions among recipients. The study concludes by emphasising the close relationship between heritage and modernity in accordance with the norms of discourse among Arabs of earlier centuries.